2016
DOI: 10.5511/plantbiotechnology.15.1219a
|View full text |Cite
|
Sign up to set email alerts
|

Induction of tetraploid hardy rubber tree, <i>Eucommia ulmoides</i>, and phenotypic differences from diploid

Abstract: Polyploid plants tend to have larger organs than diploids due to the doubling of their chromosome number. However, the enlarged regions, whether cells, tissues, or individuals differ depending on the plant species or taxon, as have metabolic changes. Eucommia ulmoides is a deciduous dioecious plant natively distributed in China that accumulates trans-1,4-polyisoprene (TPI) in laticifers throughout its tissues. To induce tetraploids of E. ulmoides, colchicine treatment time and concentration were assessed for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…After chromosome doubling, polyploid plants often exhibit multiple variations and generally develop large organs, strong resistance, high crop yield, wood quality, and ornamental value ( Zhu et al, 1995 ; Leitch and Leitch, 2008 ; Tiku et al, 2014 ). However, after polyploidization, the changes in plant height differ among species; there is usually a fast growing type ( Ni et al, 2009 ; Miller et al, 2012 ; Dai et al, 2015 ; Liao et al, 2016 ) and a dwarf type ( Mu et al, 2012 ; Tokumoto et al, 2016 ; Xue et al, 2017 ). Similar to fast growth, dwarfing is a common phenomenon in tetraploid plants, especially woody plants.…”
Section: Introductionmentioning
confidence: 99%
“…After chromosome doubling, polyploid plants often exhibit multiple variations and generally develop large organs, strong resistance, high crop yield, wood quality, and ornamental value ( Zhu et al, 1995 ; Leitch and Leitch, 2008 ; Tiku et al, 2014 ). However, after polyploidization, the changes in plant height differ among species; there is usually a fast growing type ( Ni et al, 2009 ; Miller et al, 2012 ; Dai et al, 2015 ; Liao et al, 2016 ) and a dwarf type ( Mu et al, 2012 ; Tokumoto et al, 2016 ; Xue et al, 2017 ). Similar to fast growth, dwarfing is a common phenomenon in tetraploid plants, especially woody plants.…”
Section: Introductionmentioning
confidence: 99%
“…Another species producing an important metabolite, trans-1,4-polyisoprene (TPI), used as an industrial raw material, is E. ulmoides. Studies of the effect of polyploidisation on TPI content in this species showed no significant differences between tetraploids and diploids [67].…”
Section: Effects Of Polyploidisation On the Amount And Composition Of Secondary Plant Metabolitesmentioning
confidence: 68%
“…Equally high genome doubling efficiency was obtained for Nicotiana alata J. Link and C. Otto and Eucommia ulmoides Oliver by soaking the seeds in a 0.5% colchicine solution for 48 h [66,67]. Dhamayanthi and Gotmare [68] treated seeds as well as seedlings and stem cuttings with colchicine to induce tetraploids of Gossypium armourianum Kearney and G. aridum Rose and Standley and found that seeds are the most suitable plant material in inducing polyploidy.…”
Section: Type Of Plant Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…Larger cells and more cellular content can accumulate more energy for their growth and development. Qualitative differences in morphology, growth, and physiology and biochemistry among ginkgos of different ploidy follow the laws of ploidy, as has been demonstrated on Liriodendron sino-americanum [ 36 ], Eucommia [ 37 ], rice [ 38 ], Rhododendron fortunei [ 39 ], and Thymus vulgaris [ 40 ]. However, this is not absolute; for example, the size of pure tetraploid apples ( Malus × domestica ) and Citrus limonia are smaller compared to their diploid counterparts [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 93%